Utility of Hypoglycemic Agents to Treat Asthma with Comorbid Obesity - Derek Ge; Dinah Foer; Katherine N. Cahill (Pulmonary Therapy, 2022)
Abstract Adults with obesity may develop asthma that is ineffectively controlled by inhaled corticosteroids and long-acting beta-adrenoceptor agonists. Mechanistic and translational studies suggest that metabolic dysregulation that occurs with obesity, particularly hyperglycemia and insulin resistance, contributes to altered immune cell function and low-grade systemic inflammation. Importantly, in these cases, the same proinflammatory cytokines believed to contribute to insulin resistance may also be responsible for airway remodeling and hyperresponsiveness. In the past decade, new research has emerged assessing whether hypoglycemic therapies impact comorbid asthma as reflected by the incidence of asthma, asthma-related emergency department visits, asthma-related hospitalizations, and asthma-related exacerbations. The purpose of this review article is to discuss the mechanism of action, preclinical data, and existing clinical studies regarding the efficacy and safety of hypoglycemic therapies for adults with obesity and comorbid asthma.